Risk behaviors in substance use disorder in a sample of Egyptian female patients with or without symptoms of attention-deficit hyperactivity disorder - Amany Haroun El Rasheed; Mohamed Hossam el-din Abd el moneam; Fairouz Tawfik; Radwa Walid Mohamed Farid; Hanan Elrassas (Middle East Current Psychiatry, 2023)
Abstract Background Risk-taking behaviors are associated with attention-deficit hyperactivity disorder (ADHD) and substance use disorder (SUD). Individuals with both diagnoses have been reported to have an earlier onset, a longer course, and greater severity, with more relapses and greater difficulty remaining abstinent. The current study was assessing females seeking treatment for SUDs for the presence of comorbid ADHD, to investigate the association between severity of SUD and co-occurring ADHD symptoms and to examine related risk behaviors. Therefore, thirty female patients were enrolled, and demographic data was collected. Participants were interviewed by SCID I, addiction severity index, Arabic-translated and validated version of the adult ADHD Self-Report Scale Barratt Impulsiveness Scale Version 11, and Arabic version of the Adult Scale of Hostility and Aggression. Results Thirty female patients were included in the study, and 33.3% had extreme severity, on the addiction severity index scale. Fifteen patients had ADHD symptoms; 33.3% had high likely scores, according to Adult ADHD Self-Reported Scale (ASRS). There is a significant difference regarding the age of onset of substance use and smoking (P = 0.029), first sexual activity (P = 0.002), number of sexual partners (P = 0.009), impairment in employment, and family and social relationships items (P = 0.024, P = 0.028, respectively) in SUD patients with ADHD symptoms than in SUD patients without ADHD symptoms. Conclusion Female patients diagnosed with adult ADHD have an earlier age of smoking and substance use, having first sexual activity at younger age, and having more sexual partners with more employment, family, and social relationship problems.